AKUNTANSI SYARIAH: PENDEKATAN SEJARAH - Hasnidar Hasnidar (LPPM Universitas Putera Batam, 2019)
The birth of shariah accounting paradigm can not be separated from the factors of development of Islamic economic discourse and sharia financial system that began to emerge since the mid-1990s. For some, shari'ah accounting is something that is